Inhibition of P-glycoprotein function and expression by kaempferol and quercetin - P. Limtrakul (2018)
The 170 kDa plasma membrane P-glycoprotein (Pgp) causes the efflux of chemotherapeutic drugs from cells and is believed to be an important mechanism in multidrug resistance (MDR) in human cancer. This study demonstrates that some putative flavonoids, i.e., flavonols (quercetin and kaempferol) and isoflavones (genistein and daidzein) markedly increase the sensitivity of the multidrug-resistant human cervical carcinoma KB-V1 cells (high Pgp expression) to vinblastine and paclitaxel dose-dependently, and also decrease the relative resistance of these anticancer-drugs in KB-V1 cells. None of the flavonoids had a significant effect on vinblastine and paclitaxel cytotoxicity in wildtype drug-sensitive KB-3-1 cells (lacking Pgp). These flavonoids also caused an increase in intracellular accumulation, and reduced the efflux of Rh123 and3[H]vinblastine in KB-V1 cells, but not in KB-3-1 cells. The flavonols increased the inhibitory effectiveness of Pgp activity in MDR KB-V1 cells more than isoflavones. Only treatment with flavonols up to 48 h was able to significantly decrease the Pgp expression in a dose-dependent manner in KB-V1 cells. These findings provide evidence that flavonols reduced Pgp expression and function resulting in the inhibition of Pgp activity, but isoflavones modulated intracellular drug levels by inhibiting Pgp function with no effect on Pgp expression. Among the flavonoids tested, flavonols, particularly kaempferol, exhibit the most potent MDR reversing property in KB-V1 cells. © E.S.I.F.T. srl - Firenze.